Behavior of humpback whales, Megaptera novaeangliae (Cetacea: Balaenopteridae): comparisons between two coastal areas of Brazil - Lunardi, Diana G. (2008)
Behavior of humpback whales was observed during the reproductive period off the northern coast of the state of Bahia (NB, n = 378 groups) and at the Abrolhos Bank (AB, n = 919) to compare patterns and group composition between the two locations. Alone individuals and dyads were most often encountered in both areas, although mother-calf pairs were more common in AB. While these two regions comprise distinct concentrations of humpback whales, with intrinsic environmental differences, behavior patterns were quite similar. The only behavioral differences found where for "tail up" and "resting". The patterns found here may reflect differences in the protection status of the areas or intrinsic environmental differences.